Women's Representation in Parepare's 2024 Election: Affirmative Action, Voter Perceptions, and Islamic Law - Dirga Achmad; Astinah; Azlan Thamrin; Rustam Magun Pikahulan; Muhammad Farham (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study examines the effectiveness of affirmative action and voter perceptions of women's representation in the 2024 Parepare City DPRD election from the perspectives of fiqh siyasah and maqāṣid al-sharī'ah. It employed mixed methods with an explanatory sequential design, integrating a voter survey, interviews with election administrators, political parties, and women legislative candidates, and documentary analysis. The findings indicate that the minimum 30% quota has not yet yielded substantive representation of women. Women accounted for only 24% of elected members, while several political parties did not consistently meet the quota in every electoral district. Downward rounding, weak party support, tokenism, limited campaign resources, and gender stereotypes were the principal barriers. Voter perceptions are shifting from identity politics toward performance-based politics, with capacity, integrity, track record, and tangible impact serving as the main considerations. From the perspective of fiqh siyasah, affirmative action constitutes siyasah shar'iyyah aimed at realizing justice and public benefit. Regulatory reform, stronger cadre development, equal political support, and competency-based voter education are therefore required.